The Role of Digital Online Communication, Mobile Social Media, Word of Mouth on Customer Loyalty at Tindo Store - Ambadatu, Gracelia Betania; Paridi, Andryanus; Londong, Jerliyen Pramita (PT FORMOSA CENDEKIA GLOBAL, 2024)
This research is a quantitative study which aims to determine the simultaneous and partial influence of the marketing mix consisting of digital online communication, mobile social media and word of mouth on customer loyalty to Tindo Store t-shirt fashion products Primary and secondary data for this study were collected directly from respondents' questionnaires. Parents and youth groups from both inside and outside of Toraja make up the research's population. Thirty respondents were selected for the study's sample using the purposive sampling technique. The Partial Least Square 3.0 (PLS) approach is the data analysis technique used. Based on the findings of the PLS30 analysis, it was determined that digital online communication has a significant impact on customer loyalty, with a value of 93.4%; mobile social media has an insignificant impact, with a value of 0.14%; and word-of-mouth has an insignificant impact, with a value of 0.37%. Using PLS30, it was determined that digital online communication has a significant impact on customer loyalty, with a value of 88.9%.